(3eHGOF EOGQI GdCYeGd (B:s (3eHGOF h eOGNd GdGOGQI h hXGFagG aj GdbQf GdMGOj h GdYTQjf (B/s - (3GdOhQj, RcQjGs; (3GdScGQfI, HdGd Ndas; (3GdYRGhj, fLe s ((3YeGf(B: s (3OGQ GdjGRhQj(B, s, 2010)
(3GSGSjGJ GdGOGQI , JWhQ GdacQ GdGOGQj , GdJNWjW , GdJUeje GdJfXjej , GdJhLjg (B( (3GdGJUGd , GdbjGOI , GdJMVjQ (B) (3, GdQbGHI GdGOGQjI , GdeOGNd GdGNdGbjI h GdeYQajI aj GOGQI GdefXeGJ , GdeNGd GdJbfjI GdeYGUQI aj GOGQI GdefXeGJs
(3eQGLY U(B.423 (3;GdLOGhd U(B.212 (3,(B311s
Keywords: (3EOGQI GdCYeGds; (3GdEOGQIs; (3GdQbGHI GdGOGQjIs